2004
DOI: 10.1111/j.1469-0691.2004.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes and clinical manifestations of invasive group B streptococcal infections in western Sweden 1998-2001

Abstract: This study monitored the serotypes of Streptococcus agalactiae (group B streptococcus; GBS) isolated from invasive infections in western Sweden and investigated possible relationships between serotype, age and clinical manifestations. Invasive GBS isolates were collected prospectively during 1998-2001 at six laboratories, covering two counties with a population of 1.8 million, and were serotyped by coagglutination. Clinical data were obtained from hospital notes. In total, 161 invasive strains (50 from neonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 47 publications
(81 reference statements)
7
58
4
Order By: Relevance
“…This different finding is still unclear but confirms the higher degree of variability of serotypes in distinct regions even within the same country. Overall, serotype V was described elsewhere as an important serotype causing invasive infections in adults (21,39,40,48). In this study, serotype V was also identified among adult patients, but most of them consisted of colonizing isolates (15 of 21).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This different finding is still unclear but confirms the higher degree of variability of serotypes in distinct regions even within the same country. Overall, serotype V was described elsewhere as an important serotype causing invasive infections in adults (21,39,40,48). In this study, serotype V was also identified among adult patients, but most of them consisted of colonizing isolates (15 of 21).…”
Section: Discussionmentioning
confidence: 70%
“…Data collected from different geographic areas revealed considerable variation in the phenotypic and genotypic characteristics of GBS isolates (15,18,21,22,23,24,30,31,39,42,45). In Brazil, data on the distribution of serotypes, as well as the molecular epidemiology of GBS isolates, are still scarce.…”
Section: Discussionmentioning
confidence: 99%
“…We also gathered data on potential explanatory variables (ie, variables that might explain variance in incidence or risk of group B streptococcus; 21 Andersen et al 22 Ekelund et al 23 Kuhn et al 24 Fluegge et al 25 Berardi et al 26 Trijbels-Smeulders et al 27 van den Hoogen et al 28 Hasseltvedt et al 29 Hajdu et al 30 Neto et al 31 Janek et al 32 Carbonell-Estrany et al 33 Lopez Sastre et al 34 Andreu et al 35 Persson et al 36 Heath et al 37 Oddie et al 38 Weisner et al 39 Vergnano et al 40 Subtotal (I 2 =98·6%, p=0·000)…”
Section: Data Extractionmentioning
confidence: 99%
“…Strakova et al 21 Fluegge et al 25 Berardi et al 26 Trijbels-Smeulders et al 27 Hasseltvedt et al 29 Hajdu et al 30 Neto et al 31 Carbonell-Estrany et al 33 Persson et al 36 Heath et al 37 Oddie et al 38 Weisner et al 39 Subtotal (I 2 =87·8%, p=0·000)…”
Section: Year Europementioning
confidence: 99%
“…There are major differences between countries in the distribution of GBS serotypes. In the USA, Germany and Sweden, the most common serotypes isolated from infants and colonized mothers have been types Ia, III, and V (Persson et al, 2004;Brimil et al, 2006;Harrison et al, 1998). Serotype V strains emerged in the 1990s as a frequent cause of neonatal sepsis and adult diseases in the USA.…”
Section: Introductionmentioning
confidence: 99%